Conditioned Placebo- and Nocebo-Like Effects in Adolescents: The Role of Conscious Awareness, Sensory Discrimination, and Executive Function - Neuenschwander, Regula; Weik, Ella; Tipper, Christine M.; Jensen, Karin; Oberlander, Tim F. (Frontiers in Psychiatry, 2020)
Background. Conditioning is a key mechanism of placebo and nocebo effects in adults. Little is known about the underlying mechanisms of placebo and nocebo effects in youth and how they might be influenced by conscious awareness and cognitive abilities. In this study, the role of conditioning on thermal perception in youth was investigated. Methods. Differences in thermal ratings were assessed in response to consciously and non-consciously perceived cues that were conditioned to either low or high heat. Furthermore, we tested whether executive function mediates the effect of conditioning on thermal perception. Thirty-five high-school students (14-17yrs) completed an executive function task and underwent a sensory perception paradigm. In a conditioning phase, two distinct neutral faces (conditioned cues) were coupled to either a low or a high temperature stimulus delivered to participants’ forearms. In a testing phase, the conditioned cues, and another novel face (control), were paired with identical moderate thermal stimuli. In this testing phase, for half of the participants cues were presented consciously (supraliminally) and for the other half non-consciously (subliminally). Results. We found a significant main effect of cue type on thermal ratings (p=.003) in spite of identical heat being administered following all cues. Post-hoc analyses indicated that the nocebo-like effect (conditioned high cue compared to control) was significant (p=.027); the placebo-like effect (conditioned low cue compared to control) was non-significant. No difference between cues presented supra- vs. subliminally and no significant interaction effects were found. The association between sensory discrimination and the magnitude of the nocebo-like effect was mediated by executive function. Conclusions. To our best knowledge, this is the first study establishing a relationship between thermal perception, nocebo effects, and executive function in youth. Our results may have important implications for understanding cognitive/ learning processes involved in nocebo effects.